1990
DOI: 10.1177/0021886390263008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Organization Development Consulting Competence from the Myers-Briggs Type Indicator and Stage of Ego Development

Abstract: A 77-item Consulting Competence Survey was developed and tested for reliability and validity. During a six-month course designed to help members of a corporate quality staff develop organization development (OD) skills, 64 trainees were each assessed by two of their peers using this instrument. The trainees were also assessed by two trainers using a five-item trainer rating instrument. Two dependent measures-peer rating and trainer rating-were used to test hypotheses about the predictive validity of the eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…In a large quasi-experimental study (Vincent et al 2013) we found Intuition (as measured by the Myers Briggs Type Indicator-MBTI) was associated with higher consciousness development when compared to the opposite (Sensing) preference. This association was also found in a study by Bushe and Gibbs (1990). However, we found no other associations between consciousness development and any other MBTI preferences or combinations thereof (Vincent et al 2013).…”
Section: Personality-related Readiness Factorssupporting
confidence: 89%
“…In a large quasi-experimental study (Vincent et al 2013) we found Intuition (as measured by the Myers Briggs Type Indicator-MBTI) was associated with higher consciousness development when compared to the opposite (Sensing) preference. This association was also found in a study by Bushe and Gibbs (1990). However, we found no other associations between consciousness development and any other MBTI preferences or combinations thereof (Vincent et al 2013).…”
Section: Personality-related Readiness Factorssupporting
confidence: 89%
“…In a sample of 24 managers from one organization engaged in transformative change, Mehltretter (1995) did not find a significant relationship between manager's developmental order and co-workers' perceptions of whether the manager contributed to the organization's transformation in an exemplary way. Bushe & Gibbs (1990) studied how developmental order was related to change-oriented consulting competence in a sample of OD consultants. Although not leaders with formal authority, OD consultants often play leadership roles in organizational change initiatives.…”
Section: Loevinger and Torbertmentioning
confidence: 99%
“…From a practical point of view, if further development to the advanced ego stages were possible, then its facilitation would enable a greater number of adults to experience the advantages found to be associated with advanced ego stage functioning. These advantages include greater competence and health of marital interaction style among couples (Zilbermann, 1984); among mothers, higher levels of nurturance, support, and understanding of infant children (Biekle, 1979;Dayton, 1981) and affective enabling of adolescent daughters (Hauser, Powers, & Noam, 1991); higher levels of competence, more effective problem definition, and more use of collaborative decision making among managers (Bushe & Gibbs, 1990;Merron, 1986;Smith, 1980); and higher levels of physical selfcare among the aged (Gast, 1984;Michaelson, 1985). The theoretical and research literature provides little clarification regarding the question of whether advanced ego development can and does occur in adulthood.…”
mentioning
confidence: 99%